Management And Administration: Comprehensive Review of Governance Models and Organizational Adaptability in Health Systems - Alshareef, Ali Hussain Mohammed; Alabbas, Khaled Hadi; Al-Daghrir, Saleh Ahmed Ali; Alshareef, Ali Alhassan Ali; Alsharif, Naji Saud Naji; Alsharief, Ibrahim Abdullah; Alshrief, Abdullah Hassan; Alsharif, Hussain Yahya Obud; Al faran, Mahdi Hussein Mesfar; Alshareef, Ali Abdullah Abdulwahab (Journal of Ecohumanism, 2024)
Healthcare systems and organizational change, together with governance models, remain vital to understanding the stability of health systems. This review further looks into the various forms of governance in the healthcare systems in different countries across the globe, with the effects of these governance models on the system’s performance examined. Lastly, organizational flexibility is also considered when availing health systems for emerging health challenges. Discussing centralized, decentralized, and hybrid governance models, the paper evaluates the strengths and weaknesses of the corresponding approach. Furthermore, it also points out the chief trends of the evolving healthcare system and the emergence of a more adaptable and responsive culture, particularly in the era that has experienced pandemics. The review also discusses the opportunities for technology use, public-private partnerships, and workforce training to enhance the organization’s resilience to health systems. Implications of the present study are that good governance, combined with a well-coordinated and adaptable system, augments health, productivity, and access for the public. The review ends by recommending better governance structures, flexibility, and system issues in healthcare delivery.